2022
DOI: 10.1111/1471-0528.17063
|View full text |Cite
|
Sign up to set email alerts
|

Risk of obstetric anal sphincter injury among women who birth vaginally after a prior caesarean section: A state‐wide cohort study

Abstract: Objective: Vaginal birth after caesarean (VBAC) has been suggested to be associated with an increased risk of obstetric anal sphincter injury (compared with primiparous women who birth vaginally). However, prior studies have been small or have used outdated methodology. We set out to validate whether the risk of obstetric anal sphincter injury among women having their first VBAC is greater than that among primiparous women having a vaginal birth.Design: State-wide retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Studies by Elvander et al (2019) showed that women undergoing vaginal birth after cesarean (VBAC) compared to nulliparous women have an increased risk of severe perineal injury (regardless of the indications and date of the primary cesarean section)-OR = 1.40 [19]. Uebergang et al (2021) also emphasize that women after the first VBAC have a significantly increased risk of third-or fourth-degree perineal injuries compared to primiparous women that had natural labor [20]. The results of our own research are consistent with those presented above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Elvander et al (2019) showed that women undergoing vaginal birth after cesarean (VBAC) compared to nulliparous women have an increased risk of severe perineal injury (regardless of the indications and date of the primary cesarean section)-OR = 1.40 [19]. Uebergang et al (2021) also emphasize that women after the first VBAC have a significantly increased risk of third-or fourth-degree perineal injuries compared to primiparous women that had natural labor [20]. The results of our own research are consistent with those presented above.…”
Section: Resultsmentioning
confidence: 99%
“…It should be emphasized that in the literature on the subject, there are numerous reports of spontaneous perineal trauma, in particular, severe perineal trauma. Perineal lacerations of the third and fourth degree are the most severe forms of spontaneous perineal trauma, and at the same time, are associated with numerous negative and long-term consequences for women's health [5,9,[13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…73 papers were excluded after abstract reading, either because the abstract was not relevant or because only poster or abstract existed and no full article could be found. During full‐text reading of the remaining 44 articles, 23 were found to be eligible for inclusion in the meta‐analysis 1–10,14–26 . The reasons for excluding 21 articles after full‐text reading were “no primiparous control group”, “VBAC not investigated”, “OASI risk not investigated”, “no numbers on either primiparous or VBAC” or “overlap between studies”.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies provided information on OASI in the primiparous group as well as in the VBAC group. However, in one study VBAC women might have had more than one previous caesarean section 9 and in 11 studies it was not clearly stated if the VBAC women had given birth vaginally before 1,5,10,15,16,18,19,21,24–26 . All studies clearly defined the parity of the women that we use as control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation